A De Novo Mutation in DYRK1A Causes Syndromic Intellectual Disability: A Chinese Case Report - Qiao, Fengchang; Shao, Binbin; Wang, Chen; Wang, Yan; Zhou, Ran; Liu, Gang; Meng, Lulu; Hu, Ping; Xu, Zhengfeng (Frontiers in Genetics, 2019)
Autosomal dominant mental retardation-7 (MRD7) is a rare anomaly, characterized by severe intellectual disability, feeding difficulties, behavior abnormalities, and distinctive facial features, including microcephaly, deep-set eyes, large simple ears, and a pointed or bulbous nasal tip. Some studies show that the disorder has a close correlation with variants in DYRK1A. Herein we described a Chinese girl presenting typical clinical features diagnosed at 4 years old. Whole-exome sequencing of the familial genomic DNA identified a novel mutation c.930C > A (p.Tyr310*) in exon 7 of DYRK1A in the proband. The nonsense mutation was predicted to render the truncation of the protein. Our results suggested that the de novo heterozygous mutation in DYRK1A was responsible for the MRD7 in this Chinese family, which both extended the knowledge of mutation spectrum in MRD7 patients and highlighted the clinical application of exome sequencing.